Low Dose-Extended Letrozole Versus Double Dose-Short Letrozole Protocol for Ovulation Induction in Polycystic Ovary Syndrome - S S, Shreya Varshni; Jeyamani, B; Priya, G. Prema (Journal of Neonatal Surgery, 2025)
Objective: Polycystic ovary syndrome is a prevalent endocrine disorder and a leading cause of anovulatory infertility. Letrozole, a third-generation aromatase inhibitor, has been widely adopted as the first-line pharmacological agent for ovulation induction. However, the optimal dosage and duration of letrozole administration remain under debate. This study aims to compare the efficacy of a low-dose extended letrozole regimen, 2.5 mg for 10 days, versus a double-dose short letrozole regimen, 5 mg for 5 days, in ovulation induction among women with polycystic ovary syndrome, focusing on ovulation rates, endometrial thickness, follicular response, and pregnancy outcomes. Methods: This prospective, randomized controlled study was conducted on 120 women with polycystic ovary syndrome undergoing ovulation induction at a tertiary infertility center. Participants were randomly allocated into two equal groups: group A, receiving low-dose extended letrozole at 2.5 mg for 10 days, and group B, receiving double-dose short letrozole at 5 mg for 5 days. Serial transvaginal ultrasound monitoring was performed to assess follicular growth, ovulation occurrence, and endometrial development. The primary outcome was the ovulation rate, while secondary outcomes included endometrial thickness, number of mature follicles, and pregnancy rates. Statistical analysis was performed using SPSS software, and a p-value of less than 0.05 was considered statistically significant. Results: The ovulation rate was significantly higher in group A, 85 percent, compared to group B, 72 percent, with a p-value of 0.04. Endometrial thickness on the day of ovulation was 8.9 plus or minus 1.2 millimeters in group A and 7.6 plus or minus 1.4 millimeters in group B, with a p-value of 0.02, suggesting a more favorable endometrial environment with the low-dose extended regimen. The mean number of mature follicles was comparable between the groups, 1.8 plus or minus 0.6 in group A versus 2.0 plus or minus 0.7 in group B, with a p-value of 0.09. The clinical pregnancy rate was significantly higher in group A, 41.7 percent, compared to group B, 28.3 percent, with a p-value of 0.03, indicating superior reproductive outcomes with the extended letrozole regimen Conclusion: The findings of this study demonstrate that a low-dose extended letrozole regimen of 2.5 mg for 10 days is more effective than a double-dose short letrozole regimen of 5 mg for 5 days for ovulation induction in women with polycystic ovary syndrome. The extended regimen was associated with higher ovulation rates, improved endometrial thickness, and increased pregnancy success. Given its superior efficacy and endometrial receptivity benefits, the extended letrozole protocol should be considered a viable alternative for ovulation induction in the management of polycystic ovary syndrome.